2010
DOI: 10.1107/s0021889810008150
|View full text |Cite
|
Sign up to set email alerts
|

Cation distribution in spinel (Mn,Co,Cr)3O4at room temperature

Abstract: As part of a study of the long‐term operation of solid‐oxide fuel cells, three (Mn,Co,Cr)3O4 samples have been synthesized and characterized. X‐ray and neutron diffraction patterns from the powder samples at room temperature were measured and the data were co‐refined. The neutron data were indispensible in locating Mn, Co and Cr within the crystallographic unit cell with their respective atomic occupancies. Two of these samples have been identified as cubic Mn0.76Co0.58Cr1.66O4 and Mn1.28Co1.72O4. The third is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
4
10
0
Order By: Relevance
“…The crystal structure of MnCoCrO 4 at high temperature is also a single cubic phase with space group Fd3true¯m(227), and its lattice parameter expanded with increasing the temperature. As for the occupancy preference, our result of Cr is also consistent with that in Mn 0.4 Co 0.6 Cr 2 O 4 spinel, the composition of the outer reaction layer, in which Cr 3+ occupy the octahedral sites analyzed at room temperature . Similar to Mn 1.5 Co 1.5 O 4 , the occupancy of Co on the tetrahedral site was much greater than that of Mn in MnCoCrO 4 .…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…The crystal structure of MnCoCrO 4 at high temperature is also a single cubic phase with space group Fd3true¯m(227), and its lattice parameter expanded with increasing the temperature. As for the occupancy preference, our result of Cr is also consistent with that in Mn 0.4 Co 0.6 Cr 2 O 4 spinel, the composition of the outer reaction layer, in which Cr 3+ occupy the octahedral sites analyzed at room temperature . Similar to Mn 1.5 Co 1.5 O 4 , the occupancy of Co on the tetrahedral site was much greater than that of Mn in MnCoCrO 4 .…”
Section: Resultssupporting
confidence: 84%
“…Consistent with Yang et al . 's results, at room temperature Mn 1.5 Co 1.5 O 4 consists of two phases: cubic Co‐rich Mn 1+α Co 2−α O 4 (Space group: Fd3true¯m) and tetragonal Mn‐rich Mn 2−δ Co 1+δ O 4 (Space group: I 4 1 / amd ) . As Cr content increases, the amount of the tetragonal phases also decreases, and when the Cr content is greater than 1, Mn 1.5−0.5 x Co 1.5−0.5 x Cr x O 4 forms the single cubic phase.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Chromium is known to have the strongest octahedral site preference among the transition metal cations [60,61] and is consequently expected to occupy only octahedral sites, viz. (Co)[Mn,Cr] 3 O 4 [12,59]. The higher Co/Mn fraction in the reaction layer compared to the as-prepared coating suggests that outward diffusing Cr from the alloy primarily replaces Mn in the spinel, as expected from the site preference.…”
Section: Growth and Implications Of The Cr-rich Reaction Layermentioning
confidence: 97%
“…Overall, the Co/Mn fraction in the reaction layers is greater than the Co/Mn fraction in the as-prepared coating. Cation distribution studies of MnCo 2 O 4 have shown that Mn primarily occupies the octahedral sites in the spinel structure while the tetrahedral sites are mostly filled by Co [10,58,59]. The distribution may be written as (Co)[Mn,Co]O 4 , where the round brackets designate tetrahedral sites and the square brackets designate octahedral sites.…”
Section: Growth and Implications Of The Cr-rich Reaction Layermentioning
confidence: 99%